The Effect of a Resistance Training Course on Blood Pressure and Nitric Oxide Levels in Elderly Women - Alireza Behjati Ardakani; Ahmad Qassemian; Maryam Koushki; Elham Shakour; Ahmad Mehrez (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Endothelial function is an important factor in the assessment of atherosclerosis, lipid deposition in the inner walls of the arteries, high blood pressure, and heart failure. Vascular endothelial cells play an important role in regulating vascular activities by producing substances such as nitric oxide to stimulate vessels. Methods & Materials The current study was attempted to find out the effect of resistance training on old women’s plasma nitric oxide levels and blood pressure. Twenty-four postmenopausal women (age: 67.37±6.02, BMI=26.87±4.16, and WHR=0.92±0.4 mean±SD) were selected objectively and divided into control (n=12) and experimental (n=12) groups randomly. Experimental group performed resistance training for eight weeks, three sessions per week with 40-65% intensity. Study variables were measured and recorded before and after training program. Paired and independent sample t tests were used for data analysis. The significance level was lower than 0.05. Results  The results revealed that resistance training had a significant effect on nitric oxide levels (P=0.01) and blood pressure (P=0.006, P=0.002) in old women.  Conclusion A period of resistance training with present study characteristics can reduce both systolic and diastolic hypotension and increase plasma nitric oxide levels, and therefore is recommended for prevention of cardiovascular diseases, atherosclerosis, and hypertension in old women.